PERFORMANCE ANALYSIS OF STEEL PILES ON EXISTING BERTHING DOLPHIN STRUCTURE - Yus, Bella Esfadiary; Fathani, Faisal; Faris, Fikri (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2025)
East Kalimantan Province, located on Indonesias largest coal-exporting island, relies heavily on the Mahakam River as a major water transportation route. In a jetty construction project along a tributary of the Mahakam River in East Kalimantan, modifications were made to the structure from the original design, presumably contributing to the dolphin structure's displacement. Soil test data indicate predominantly clayey soil, with hard layers at approximately 20 m depth. This study aims to evaluate the structural strength of the initial design and the existing condition through manual calculations and SAP2000 analysis. Manual calculations utilize N-SPT values, while SAP2000 models soil as a spring element based on the Nakazawa Method. The study evaluates the existing dolphin structure using numerical modelling and manual calculations, showing an increase in vertical capacity from 231.17kN to 302.82 kN and a reduction in displacement from 43.3mm to 23.3mm. Despite depth modifications from the original design, the berthing dolphin structure remains structurally safe for its intended function.East Kalimantan Province, located on Indonesias largest coal-exporting island, relies heavily on the Mahakam River as a major water transportation route. In a jetty construction project along a tributary of the Mahakam River in East Kalimantan, modifications were made to the structure from the original design, presumably contributing to the dolphin structure's displacement. Soil test data indicate predominantly clayey soil, with hard layers at approximately 20 m depth. This study aims to evaluate the structural strength of the initial design and the existing condition through manual calculations and SAP2000 analysis. Manual calculations utilize N-SPT values, while SAP2000 models soil as a spring element based on the Nakazawa Method. The study evaluates the existing dolphin structure using numerical modelling and manual calculations, showing an increase in vertical capacity from 231.17kN to 302.82 kN and a reduction in displacement from 43.3mm to 23.3mm. Despite depth modifications from the original design, the berthing dolphin structure remains structurally safe for its intended function.